1992
DOI: 10.3758/bf03202713
|View full text |Cite
|
Sign up to set email alerts
|

The influence of retrieval on retention

Abstract: Four experiments tested the hypothesis that successful retrieval of an item from memory affects retention only because the retrieval provides an additional presentation of the target item. Two methods oflearning paired associates were compared. In the pure study trial (pure ST condition) method, both items of a pair were presented simultaneously for study. In the test trial/study trial (ITST condition) method, subjects attempted to retrieve the response term during a period in which only the stimulus term was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
416
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 487 publications
(447 citation statements)
references
References 38 publications
27
416
0
4
Order By: Relevance
“…For the 32 included studies, a weighted average across experiments was constructed for each condition, depending on sample size. Appendix A contains a full listing of all studies, with sample size, and all populations studied, including other specialized samples (e.g., depressed patients, ADHD) not included in the fi gure Such a dynamic would still constitute an interesting an important determinant of which traces ultimately survive in memory because rehearsal and reactivation are key factors thought to enhance longevity of our experiences (Allen, Mahler, & Estes, 1969 ;Bjork, 1975 ;Carrier & Pashler, 1992 ;Karpicke & Roediger, 2008 ;Landauer & Bjork, 1978 ) . Indeed, some have built the case that selective prevention of retrieval, by itself, is a key process of motivated forgetting (Erdelyi, 1996 ) .…”
Section: Stopping Retrieval: Basic Behavioral Findingsmentioning
confidence: 99%
“…For the 32 included studies, a weighted average across experiments was constructed for each condition, depending on sample size. Appendix A contains a full listing of all studies, with sample size, and all populations studied, including other specialized samples (e.g., depressed patients, ADHD) not included in the fi gure Such a dynamic would still constitute an interesting an important determinant of which traces ultimately survive in memory because rehearsal and reactivation are key factors thought to enhance longevity of our experiences (Allen, Mahler, & Estes, 1969 ;Bjork, 1975 ;Carrier & Pashler, 1992 ;Karpicke & Roediger, 2008 ;Landauer & Bjork, 1978 ) . Indeed, some have built the case that selective prevention of retrieval, by itself, is a key process of motivated forgetting (Erdelyi, 1996 ) .…”
Section: Stopping Retrieval: Basic Behavioral Findingsmentioning
confidence: 99%
“…The testing effect is the phenomenon that retrieval practice leads to better long-term retention than additional study (for reviews see e.g., Rawson & Dunlosky, 2011;Roediger & Butler, 2011;Roediger, Putnam, & Smith, 2011;Roediger & Karpicke, 2006;Rowland, 2014). As in the studies conducted on distributed practice, most experiments on retrieval practice have been conducted using word lists or word pairs (e.g., Bouwmeester & Verkoeijen, 2011;Carpenter, Pashler, & Vul, 2006;Carpenter, Pashler, Wixted, & Vul, 2008;Toppino & Cohen, 2009;Tulving, 1967;Wheeler, Ewers, & Buonanno, 2003) and foreign vocabulary pairs (e.g., Carpenter et al, 2008;Carrier & Pashler, 1992;Fritz, Morris, Acton, Voelkel, & Etkind, 2007;Karpicke, 2009;Karpicke & Roediger, 2008;Pashler, Cepeda, Wixted, & Rohrer, 2005;Pyc & Rawson, 2007Toppino & Cohen, 2009). Some studies have found a beneficial effect of retrieval practice for first language vocabulary learning, with adults (e.g., Cull, 2000;Karpicke & Smith, 2012), as well as with primary school children (e.g., Goossens, Camp, Verkoeijen, Tabbers, & Zwaan, 2014;Metcalfe, Kornell, & Son, 2007).…”
mentioning
confidence: 99%
“…It has also been found in studies of foreign-language vocabulary learning. For example, when subjects were given 5 s to try to retrieve the English equivalent of an Eskimo word, and then saw both words for 5 more seconds, later memory performance was better than when the English and Eskimo words were both available for 10 s (Carrier & Pashler, 1992). This benefit of testing over restudying-henceforth, the testing effect, also sometimes referred to as retrieval practice-has been found with learning of facts (McDaniel & Fisher, 1991), of face-name pairs (Carpenter & DeLosh, 2005), and even of visuospatial information (Carpenter & Pashler, 2007;Kang, 2010; see Roediger & Karpicke, 2006, for a review).…”
mentioning
confidence: 99%